Influence of milk-clotting enzymes of animal and microbial origin on the quality and shelf life of soft cheeses - D. S. Myagkonosov; I. T. Smykov; D. V. Abramov; I. N. Delitskaya; E. G. Ovchinnikova (Пищевые системы, 2022)
A comparative test was carried out for milk-clotting enzymes (MCE) of animal origin (Naturen® Extra), microbial origin (Marzyme®) and MCE based on recombinant camel chymosin (Chy-max® M) in the production of soft cheese “Lyubitelskiy”. By the end of the shelf life of the cheeses (12 days at a temperature of 3 ± 1 °C), differences were noted in the degree of proteolysis (DP) and the value of the complex modulus G*, which were the following ones for cheeses produced with MCE of the brands: Naturen® — DP = 17.86 ± 0.24%; G* = 4164 ± 587 Pa; Marzyme® — DP = 17.98 ± 0.49%; G* = 4581±786 Pa; Chy-max® M — DP = 9.85 ± 0.63%; G* = 7949 ± 1157 Pa. Cheeses made with Chy-max® M MCE had a denser texture than cheeses made with MCE of Naturen or Marzyme, which did not differ significantly in consistency. In the studied cheeses, the severity of the bitter taste was proportional to the content of water-soluble peptides with a mass of 0.5–3 kDa. Cheeses with Marzyme® MCE had a more intense bitterness than cheeses with Naturen® MCE. There was no bitter taste in cheeses produced with MCE of Chy-max® M. It was concluded that in the production of soft cheeses, recombinant camel chymosin can be used to increase the shelf life, and MCE of microbial origin can be recommended to replace more expensive MCE of animal origin.